Identification of Compounds from Hexane Extract of Virginia Tobacco Bark in Lombok and Its Potential as Botanical Pesticides - Sarjan, Muhammad; Supriadi, Supriadi; Rizaldi, Lalu Heri; Sarjan, Achmad Fajar Narotama (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This research aims to identify the class of terpenoid compounds contained in hexane extract of tobacco stems (Nicotiana tabacum). The extraction method uses hexane solvent to obtain terpenoid compounds contained in tobacco bark. Gas chromatography-mass (GC-MS) techniques were used to analyze and identify these compounds. The compound contained in the hexane extract of Virginia tobacco stem bark is only one terpenoid derivative, namely 4,8,13-Cyclotetradecatriene-1,3-diol. Analysis of the structure of this compound shows its potential as an antimicrobial and can be applied in the agricultural industry, namely as a botanical pesticide. Its unique chemical structure enables various mechanisms of action against microbes, which can be further explored for the development of agricultural applications. Further research is needed to fully understand the potential and mechanism of action of this compound in an antimicrobial context.